2023
DOI: 10.1038/s41598-023-28065-6
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical evaluation of the polycaprolactone-polyethylene glycol electrospun nanofibers containing egg-yolk oil for acceleration of full thickness burns healing

Abstract: Considering the great potential of egg yolk oil (EYO) in management of burn wounds and superb biological properties of polycaprolactone (PCL) and polyethylene glycol (PEG), hereby, a PCL-PEG-EYO scaffold was developed by electrospinning method for burn healing. The physico-chemical characterizations were performed using SEM, FTIR and contact angle tests. The biological properties of the fabricated scaffolds were evaluated by antibacterial test, in vitro cell culturing, MTT assay and in vivo experiments. The SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Wound monitoring using electrospun nanofibers typically involves three components: sensors, drug delivery, and support structures. 23,103 When applied to wound monitoring, sensors can detect parameters such as wound temperature, humidity, and pH, and transmit these data to external devices for analysis and processing. 184,185 When applied to wound treatment, nanofibers can release drugs, promoting wound healing and preventing infection.…”
Section: Functionality Of Electrostatically Spun Nanofiber Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wound monitoring using electrospun nanofibers typically involves three components: sensors, drug delivery, and support structures. 23,103 When applied to wound monitoring, sensors can detect parameters such as wound temperature, humidity, and pH, and transmit these data to external devices for analysis and processing. 184,185 When applied to wound treatment, nanofibers can release drugs, promoting wound healing and preventing infection.…”
Section: Functionality Of Electrostatically Spun Nanofiber Materialsmentioning
confidence: 99%
“…For example, they are used in water ltration treatment, 14 photocatalytic treatment of water pollution, 15 electrocatalysis, 16 and ltration in the eld of environmental protection. According to reports, there are already dozens of polymers that have been made into nanober structures through electrospinning technology, 17,18 such as poly-L-lactic acid (PLA), 19,20 polyvinyl alcohol (PVA), 21,22 polycaprolactone (PCL), [22][23][24][25] polyurethane (PU), 26 polyvinylidene uoride (PVDF), 27 and polyhydroxybutyric acid ester hydroxy valerate (PHBV), 28,29 which are also used in the development of electrospinning materials.…”
Section: Introductionmentioning
confidence: 99%
“…27 The dressing for burn wounds must possess adequate breathability to facilitate optimal wound healing, as indicated by previous studies. 48,107 Adequate hydrophilicity can help to maintain the appropriate moisture levels in wounds as well as soften necrotic tissues. This property also enhances the ability to promote the regeneration of skin tissue.…”
Section: Applications Of Electrospun Nanofiber Scaffolds In Stementioning
confidence: 99%
“…Studies have indicated that non-ionic hydrophilic surfaces can reduce the production of pro-inflammatory cytokines, indicating their potential to limit both leukocyte adhesion and macrophage fusion and promote regenerative inflammation [ 153 ]. Biomaterials such as poly(ethylene glycol) (PEG), HA, glycosaminoglycans, chitosan, heparin and phosphatidylcholine have been used to increase hydrophilicity and reduce protein adsorption through various processes [ 154–158 ]. Synthetic polymers such as poly(lactic acid), poly(lactic-co-glycolic acid) (PLGA) and poly(vinyl alcohol) have also shown potential for enhancing biocompatibility by limiting protein adsorption and consequently reducing NEU recruitment [ 159–161 ].…”
Section: Modulating Innate Immunity In the New Generation Of Wound-he...mentioning
confidence: 99%